Advanced Analytical Model of Strength in Quasibrittle Media - Kučera, Michal; Vořechovský, Miroslav (Vysoké učení technické v Brně,Fakulta stavební, 2024)
The purpose of this work is to extend the use of a recently developed analytical model of concrete fracture behavior to general load cases. The model reflects the stress redistribution processes in the fracture process zone by averaging the local material strength. Analytically, the probability that the spatial stress field attains the averaged strength field is obtained, resulting in a full probability density function of random structural strength, which naturally captures all sources of structural size effect. The expanded version of this model can be used in various general load cases.
Keywords: Random strength field; mesoscale; concrete; FPZ; weibull theory